Not Easy Being “Me”: Deconstructing Foreign Language Teachers’ Self Through Collaborative Autoethnography - Hernández Victoria, Juan Camilo; Diaz González, Laura Daniela; Méndez Garzón, Franz Stehf (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In this article, we, three pre-service Foreign Language teachers, used an introspective view of our memories and experiences to extract relevant aspects that defined our teacher self, teaching methodology, and vocation in Southern Colombia. We used a collaborative autoethnographic approach with virtual cumulative collaboration and an analytical/evocative typology. Our stories are evocative, but our experiences were extracted using instruments such as memory collection, self-reflections, reflective journal writing, autobiographical essays, and focus group discussions. We found tacit structural/sociological policies and factors which influenced our learning processes throughout our student selves. Factors concerning acculturation/cultural integration, affective teaching environments or lack thereof, and family dynamics influenced our selves. From retelling our stories, we can see that these policies/factors had an adverse effect in our learning, but a positive effect on our teacher selves and vocation. We can safely say that negative learning/family experiences influencedour teacher selves for the better in our stories.